Fetal Abdominal Aorta: Doppler and Structural Evaluation of Endothelial Function in Intrauterine Growth Restriction and Controls - Visentin, Silvia; Londero, Ambrogio P; Calanducci, Maria; Grisan, Enrico; Bongiorno, Maria Caterina; Marin, Loris; Cosmi, Erich (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose The human aorta stores strain energy in the distended wall during systole through the extracellular matrix of the tunica media that could be influenced by blood pressure, flow, or increased peripheral resistance. In intrauterine growth restriction (IUGR) fetuses, the increased aorta intima media thickness (aIMT) could reflect a different extracellular matrix composition and, therefore, functionality. The aim of this study was to analyze the resistance to flow in the fetal descending aorta and its relation to aIMT and systolic and diastolic fetal abdominal aorta diameters in IUGR fetuses and controls.Materials and Methods This is a prospective case control study of single pregnancies collected at a tertiary center for feto-maternal medicine in Northeast Italy. An IUGR group as cases and a group of fetuses appropriate for gestational age (AGA) as controls were included.Results We found a greater PI of the fetal abdominal aorta in the IUGR group (1.82) than in the AGA group (1.21) (p < 0.05). The change between the systolic and diastolic fetal abdominal aorta diameters was significantly greater in IUGR fetuses (0.10 mm (IQR 0.07 – 0.28)) than in the AGA group (0.04 mm (0.03 – 0.05)) (p < 0.05). In the IUGR group aIMT was significantly correlated with peak systolic velocity (PSV) and systolic-diastolic aorta diameter change, while these two correlations were not found in the control group.Conclusion The change between the systolic and diastolic fetal abdominal aorta diameters in IUGR cases during the early third trimester of pregnancy was significantly increased and aIMT in the IUGR group was significantly correlated to systolic-diastolic diameter change and PSV, probably reflecting aortic wall adaptation to blood flow changes in IUGR fetuses.
Keywords: intrauterine growth restriction; fetal abdominal aorta; aorta diameter; doppler